5(3x-8)-2=-33-15x

Simple and best practice solution for 5(3x-8)-2=-33-15x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(3x-8)-2=-33-15x equation:


Simplifying
5(3x + -8) + -2 = -33 + -15x

Reorder the terms:
5(-8 + 3x) + -2 = -33 + -15x
(-8 * 5 + 3x * 5) + -2 = -33 + -15x
(-40 + 15x) + -2 = -33 + -15x

Reorder the terms:
-40 + -2 + 15x = -33 + -15x

Combine like terms: -40 + -2 = -42
-42 + 15x = -33 + -15x

Solving
-42 + 15x = -33 + -15x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '15x' to each side of the equation.
-42 + 15x + 15x = -33 + -15x + 15x

Combine like terms: 15x + 15x = 30x
-42 + 30x = -33 + -15x + 15x

Combine like terms: -15x + 15x = 0
-42 + 30x = -33 + 0
-42 + 30x = -33

Add '42' to each side of the equation.
-42 + 42 + 30x = -33 + 42

Combine like terms: -42 + 42 = 0
0 + 30x = -33 + 42
30x = -33 + 42

Combine like terms: -33 + 42 = 9
30x = 9

Divide each side by '30'.
x = 0.3

Simplifying
x = 0.3

See similar equations:

| 2b^2=-6 | | 9x^2+16=25 | | x+18x=3 | | 5(3x-8)-2=-33-15v | | 18x^3-4x^2+10x= | | 55-55= | | 6.5x+x=74 | | -6(2+a)=48 | | 6r-60=12 | | 5a^2=-13a-6 | | 7x^2-3=67 | | 6+c=22 | | c^4-9c^2+20=0 | | 5x+2=6x+-4 | | 0=9x-y+5 | | 8x^2+5x+7=0 | | Y=4x^2+2x+1 | | v^2+7v+30=0 | | z-(-40)=33 | | x+20=1/3(234) | | Y=-0.2(40)+50 | | 4x-27+(x+39)=180 | | 4X^2+2x+1=y | | x-16=2/3x | | 7x-(3x+10)=-x+15 | | 5x^2+33x=-18 | | p=5-4p | | 7x-3-2x=24-4x | | 6-(-5-11)= | | N^2+10=6 | | 2(7x-9)=3(8x-1) | | 17x-(-4x-5)=70 |

Equations solver categories